2023
DOI: 10.1021/acs.orglett.3c03222
|View full text |Cite
|
Sign up to set email alerts
|

Hantzsch Esters Enabled [2π+2σ] Cycloadditions of Bicyclo [1.1.0] butanes and Alkenes under Photo Conditions

Huaipu Yan,
Yonghong Liu,
Xiao Feng
et al.

Abstract: Hantzsch esters (HEs) are widely recognized as sources of hydride ions (H-) and sacrificial electron donors in their ground state. Here, we report the application of HE as a mediator in [2π+2σ] cycloaddition of bicyclo[1.1.0]butanes (BCBs) with alkenes under photo conditions. Through this strategy, various substituted bicyclo[2.1.1]hexanes can be efficiently prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…[46] The Shi Group developed another light-driven electron transfer method to access bicyclic bioisosteres structures, in which they prepared BCHs 134 using Hantzsch ester as the catalyst with 1-benzoyl-3-phenylbicyclobutane (133) and various alkenes 132 (Scheme 21). [47] It was proposed that photoexcited Hantzsch ester transfers a hydrogen atom or sequentially transfers an electron then proton to 133 to generate the enol radical 135. The enol radical adds into the alkene, followed by radical addition into the enol and hydrogen atom transfer to yield the BCH product and regenerate Hantzsch ester.…”
Section: Electron Transfer Catalysis To Construct Bchs and Bchepsmentioning
confidence: 99%
“…[46] The Shi Group developed another light-driven electron transfer method to access bicyclic bioisosteres structures, in which they prepared BCHs 134 using Hantzsch ester as the catalyst with 1-benzoyl-3-phenylbicyclobutane (133) and various alkenes 132 (Scheme 21). [47] It was proposed that photoexcited Hantzsch ester transfers a hydrogen atom or sequentially transfers an electron then proton to 133 to generate the enol radical 135. The enol radical adds into the alkene, followed by radical addition into the enol and hydrogen atom transfer to yield the BCH product and regenerate Hantzsch ester.…”
Section: Electron Transfer Catalysis To Construct Bchs and Bchepsmentioning
confidence: 99%
“…For instance, Mykhailiuk and co-workers showed that 2-oxabicyclo[2.1.1]­hexanes (oxa-BCHs), a potential bioisostere for meta -substituted arene rings, proved to be more hydrophilic and less lipophilic than proclaimed bicyclo[1.1.1]­pentanes. , The oxa-BCH unit is further claimed to be 30 times more hydrophilic, less lipophilic, and more stable than the corresponding parent meta -substituted benzene ring. Since the conceptual advancement of “escape from flatland”, many reports from Brown, Studer, Procter, Molander, Leitch, Aggarwal, Li, Wang, Waser, Shi, Bach, and our group , displayed BCBs as potential precursors for 3D-chemical space exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The latter, however, may in turn facilitate the rapid advance of the former. As a paradigm, the synthesis of bicyclo[2.1.1]­hexanes (BCHs) has attracted increasing attention from chemists in recent years due to the ability of these rigid hydrocarbons to serve as ideal bioisosteres of ortho or meta-substituted benzenoids (Scheme A) to improve the metabolic stability of corresponding drug analogues. As a result, a wide range of efficient intermolecular [2π + 2σ] cycloaddition reactions of bicyclo[1.1.0]­butanes (BCBs) with olefins have been developed, originating from the widespread availability of both feedstock and the ability to conveniently assemble diverse substituents on BCHs. Among them, the Procter and Wang groups have established the SmI 2 and pyridine-diboron-engaged catalytic systems, respectively, to trigger the transformations by single electron transfer (SET). , Furthermore, photocatalysis as a green and sustainable platform for radical chemistry has been leveraged by Glorius and Brown to accomplish energy transfer (EnT)-enabled cycloadditions of BCBs with various cyclic and acyclic olefins (Scheme B). , In this regard, photoredox catalysis as another powerful tool for the production of radical species has never been applied to such an important chemical transformation, and its viability may provide an opportunity to make feasible those incompatible substrates, such as simple BCBs containing phenyl ketones, in the energy transfer platform . As another noteworthy issue, a large number of BCHs contain stereocenter(s) (Scheme A), revealing that replacing benzenoids by either R - or S -enantiomers of BCHs may lead to distinct bioactivities of the drug.…”
Section: Introductionmentioning
confidence: 99%